SIMULASI GENANGAN AIR DENGAN MENGGUNAKAN SOFTWARE HEC-RAS (Studi Ruas Jalan Ampang Pulai, Kecamatan Koto XI Tarusan, Pesisir Selatan) - Nofrizal Nofrizal; Syofyan Z Syofyan Z; Jeki Tri Agusman (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
The case in the District of Koto XI Tarusan, especially in the area of the Ampang Pulai route, is a flood event that occurs almost every year during the rainy season. The flood has caused hundreds of houses, schools and office buildings to stop by up to 50 centimeters. Puddles occur when rainfall exceeds 100 millimeters or a day with 6 hours of rain.Based on the problems that have been stated, this type of research includes applied research. From the results of running the flow profile analysis using the HEC-RAS software, it is found that the drainage slope is different and at some points the drainage flow is not smooth and there is blockage in the area. Results of data analysis carried out 1. HEC-RAS is able to perform permanent and non-permanent flow simulations from water level profiles in artificial and natural channels/rivers, sediment transport analysis on a moving basis, water quality analysis and several hydraulic designs. 2. From the analysis of running flow profile analysis using the HEC-RAS software, several drainage points are found whose elevation is too low and water puddles are easy to occur at that point.